Penerapan Terapi Tertawa pada Pasien dengan Resiko Prilaku Kekerasan di Panti ODGJ Palembang - Lenni Chairani Gultom; Aprida Manurung; Novita Anggraini (Quantum Wellness : Jurnal Ilmu Kesehatan, 2026)
The risk of violent behavior is a condition where a person commits an act that can be physically dangerous, either to themselves, others or their own family. To overcome this, a special therapy is needed. Laughter therapy will release endorphins so that the body becomes more comfortable, relaxed and makes the client's emotional state better so that it can suppress the desire to get angry. This study uses a descriptive case study with a nursing process approach to 5 respondents. With laughter therapy intervention for 20-30 minutes. The intervention was carried out on June 4 to 6, 2025, located at the Palembang ODGJ shelter. Client 1(Mr. H) before the intervention there were 9 signs and symptoms of the risk of violent behavior and after the intervention it became 1. In client 2 (Mr. L) before the intervention there were 9 signs and symptoms after the intervention 0 signs and symptoms. In client 3 (Mr. A) before the intervention there were 8 signs and symptoms after the intervention 1 sign and symptom. Client 4 (Mr. F) had 7 signs and symptoms before the intervention, but after the intervention, it became 1. Client 5 (Mr. S) had 5 signs and symptoms before the intervention, but after the intervention, it became 1 sign and symptom.